2003
DOI: 10.1161/01.res.0000049105.15329.1c
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Cyclin D1 Nuclear Import in Cardiomyocyte Proliferation

Abstract: Mammalian cardiomyocytes irreversibly lose their capacity to proliferate soon after birth, yet the underlying mechanisms have been unclear. Cyclin D1 and its partner, cyclin-dependent kinase 4 (CDK4), are important for promoting the G1-to-S phase progression via phosphorylation of the retinoblastoma (Rb) protein. Mitogenic stimulation induces hypertrophic cell growth and upregulates expression of cyclin D1 in postmitotic cardiomyocytes. In the present study, we show that, in neonatal rat cardiomyocytes, D-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 37 publications
5
133
0
Order By: Relevance
“…Immunostaining of these cells showed that cyclin D1 was not expressed in the nuclei as previously reported. 12,13 By contrast, cyclin D2 expression was clearly localized in the nuclei of cells positive for a cardiac marker, suggesting that cyclin D2 is inducible in the nuclei upon serum treatment. We next examined the relative expression of cyclin D1 and D2.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Immunostaining of these cells showed that cyclin D1 was not expressed in the nuclei as previously reported. 12,13 By contrast, cyclin D2 expression was clearly localized in the nuclei of cells positive for a cardiac marker, suggesting that cyclin D2 is inducible in the nuclei upon serum treatment. We next examined the relative expression of cyclin D1 and D2.…”
Section: Resultsmentioning
confidence: 96%
“…13 Cancellation of this inhibitory mechanism, the nuclear expression of cyclin D1 (D1NLS)/CDK4, is sufficient to induce cell cycle progression leading to cell division of neonatal cardiomyocytes. In the current study, we showed that cyclin D2 is expressed in the nuclei of cardiomyocytes, consistent with a previous report.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations